From the critical to praxis: in search of a Marxism for the twenty-first century - Querido, Fabio Mascaro (Pontifícia Universidade Católica de São Paulo, 2010)
"Da miséria ideológica à crise do capital: uma reconciliação histórica", of Maria Orlanda Pinassi